SPESIFIKASI MODEL PENGUKURAN FORMATIF UNTUK MENGUJI PENGARUH NEED FOR CLOSURE KONSUMEN ONLINE PADA LEVEL - Kuntari Erimurti (Jurnal Ekonomi dan Bisnis, 2009)
Need for closure is a new construct in consumer behavior and marketing management research.This construct is considerably robust to measure consumer’s epistemic motivation.Epistemic motivation is a desire based action to obtain relevant knowledge to make judgmentor buying decision. Previous study measures need for closure construct with reflective measurementmodel specification. Conceptual analysis shows that need for closure construct isa formative model due to the equality of its dimensions. This study shows strong evidencethat formative measurement model specification is more robust than reflective model to testthe model of influence of need for closure of online consumer and flow level in the internetenvironmentKeywords : Need For Closure, Flow, Formative, Reflective, Online Consumer